Volatility, information, and double versus walrasian auction pricing in US and Japanese futures markets - Dhillon, Upinder S.; Lasser, Dennis J.; Watanabe, Taiji (Journal of Banking & Finance, 1997)
This study empirically examines volatility in US and Japanese commodity futures markets. The US futures market, COMEX, is double auction with continuous trading, whereas the Japanese futures market, TOCOM, was Walrasian with discrete trading until April 1991. We find intraday volatility for gold futures contracts to be significantly higher on COMEX than TOCOM throughout the sample period and is attributable to differences in information flows and market micro-structures. Evidence is also provided that exchange volume conveys information both within and across markets, which is consistent with the French and Roll, 1986 (French, K.R., Roll, R., 1986. Stock return variances: The arrival of information and the reaction of traders. Journal of Financial Economics 17, 5–26) private-information based rational trading model. Finally, daily variance and autocorrelation estimates within COMEX are consistent with the extant literature on equity markets.